Correlation between diabetes mellitus and number of restored, carious lesions and missing teeth: A retrospective radiographic evaluation - Soban Qadir Khan; Abdul Khabeer; Ahmad M. Al-Thobity; Mashael Abdullah Benrashed; Nujood Ibrahim Alyousef; Yara AlMaimouni (Elsevier, 2021)
Aim: This study aimed to evaluate the prevalence of carious, restored, and missing teeth among diabetic and non-diabetic patients who visited dental clinics in Dammam, Saudi Arabia. Method: This retrospective study was conducted between April and November 2018. The data collection procedure was conducted in two steps: (1) review of patient records for the demographic variables and (2) screening of digital panoramic radiographs (OPGs). The patients who visited the restorative and prosthetic clinics in the period of 2016-2017 were included in the study. Results: A total of 1186 patient records and OPGs were reviewed to extract the data. The average age of the patients in the study sample was 40.96 (±16.29). The sample included 751 (63.3%) female and 435 (36.7%) male patients. Among the patients, 192 (16.2%) had diabetes mellitus and 994 (83.8%) were non-diabetic. The average numbers of fixed partial dentures and missing teeth were significantly high among diabetic patients (P < 0.001). Conversely, the average numbers of carious lesions and restored teeth were higher among the non-diabetic patients. Only the number of restored teeth was found to be significant (P < 0.001). Conclusion: The diabetic patients were found to be at high risk of losing teeth compared with the non-diabetic patients. The prevalence of fixed partial dentures was also higher among diabetic patients. The oral health status of dental patients with diabetes needs urgent attention to prevent these patients from having teeth loss, and it can be done by improving their oral health.